Produção, purificação, caracterização e avaliação do potencial biotecnológico da endo-xilanase do fungo termofílo Humicola brevis var. thermoidea - ALINE PEREIRA DE ALMEIDA (2021)
The biodegradation of lignocellulosic biomass, particularly hemicellulose, depends on a group of enzymes called the hemicellulolytic complex, produced mainly by fungi and bacteria. Among these hemicellulases, endo-xylanases have been widely used to enhance hemicellulose in applications in bioprocesses. In this context, this work aimed to produce, purify, characterize and evaluate the biotechnological potential of Humicola brevis var. thermoidea in saccharification of lignocellulosic biomass. For this purpose, the native endo-xylanase (XylHb) was purified. The biophysical characterization of the secondary structures by circular dichroism indicated the predominance of β sheet, a typical characteristic of endo-xylanases of the GH11 family, and the intrinsic fluorescence of Trp analysis indicated that the protein has its tertiary folding with the Trp residues immersed in a hydrophobic environment. The results of the biochemical and kinetic characterizations of XylHb indicated that the study enzyme had a higher tolerance over a wide range of pH, temperature, NaCl, and ethanol, having a better performance in hydrolyzing birchwood xylan at temperatures of 50 and 60 ºC when comparing commercial xylanase (Cellic®HTec2). The hydrolysis assays of the hydrothermally pretreated sugarcane bagasse demonstrated that the supplementation of Cellic®CTec2 with XylHb showed synergistic interactions and significantly increased the release of glucose and total reducing sugars when compared to the individual Cellic®Ctec2 commercial standard. Thus, a purified XylHb from the enzymatic extract of H. brevis var. thermoidea, due to its physical-active properties, performance, and synergism with commercial cellulase, which are important characteristics for application in an industrial environment, can contribute as a promising biotechnological alternative, application, and valorization of hemicellulose in the production of bioproducts.